EFFECTIVENESS OF TRICHODERMA SPECIES IN THE MANAGEMENT OF SUGARCANE WILT (FUSARIUM SACCHARI) - FATIMA, A; KHAN, YSA; IQRA, .; TALHA, A; JAN, A; ASAD, Z; SABA, H; ASLAM, AH; BATOOL, M; ASHRAF, ZU (Biological and Clinical Sciences Research Journal, 2024)
Sugarcane is a major cash crop in Pakistan. It has a great contribution in world’s economy. Many diseases cause many losses in yield of sugarcane. Fungi are considered as abundant traitorous pathogens that obstruct the viable growth of sugarcane crop. Wilt disease caused by fungal pathogen Fusarium sacchari caused many losses in sugarcane production in Pakistan. Fusarium sacchari is a causative fungus of wilt in sugarcane. Biocontrol agent Trichoderma spp. used in the management of sugarcane wilt. These bio‐agents help in diseases management and play important role in increasing the crop yield. For this reason, these bio‐agents are used for biological maintaenace of crop diseases and research globally. The use of PDA medium in vitro revealed antagonistic activity of various Trichoderma isolates against the sugarcane wilt pathogen Pathogenicity test also executed to check the most aggressiveness strain of Fusarium spp. to cause disease in sugarcane plant. In vivo, Trichoderma multiply on different substrates and corn Cobbs is good byproduct Trichoderma multiply on it and mix in soil of pots. Pot experiment performed with different treatments to control wilt disease by using of antagonist’s to check disease incidence and disease reduction.